Long‐term maintenance of skin immune system in a NOD‐Scid IL2rγnull mouse model transplanted with human skin. Issue 11 (November 2014) - Soria, Angèle; Boccara, David; Chonco, Louis; Yahia, Nora; Dufossée, Mélody; Cardinaud, Sylvain; Moris, Arnaud; Liard, Christelle; Joulin‐Giet, Alix; Julithe, Marion; Mimoun, Maurice; Combadière, Béhazine; et al.
Abstract We developed a NOD‐Scid IL2rγnull mouse model transplanted with human skin that brings fundamental insight on in vivo cellular mechanisms of intradermal immunization and antigen presentation by dermal dendritic and epidermal Langerhans cells for skin T‐cell immunity. Indeed, T‐cell immunity is a crucial checkpoint for the induction of in vivo rapid control of skin infection. With the long‐term preservation of a complete human skin immune system, this model offers the unique opportunity not only to better understand mechanisms of skin immune response but also to test new compounds and devices for cutaneous routes of vaccination, as well as new therapeutics approach for skin diseases, allergies or infections.